2008
DOI: 10.1371/journal.pone.0003583
|View full text |Cite
|
Sign up to set email alerts
|

Concept, Design and Implementation of a Cardiovascular Gene-Centric 50 K SNP Array for Large-Scale Genomic Association Studies

Abstract: A wealth of genetic associations for cardiovascular and metabolic phenotypes in humans has been accumulating over the last decade, in particular a large number of loci derived from recent genome wide association studies (GWAS). True complex disease-associated loci often exert modest effects, so their delineation currently requires integration of diverse phenotypic data from large studies to ensure robust meta-analyses. We have designed a gene-centric 50 K single nucleotide polymorphism (SNP) array to assess po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
417
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 347 publications
(424 citation statements)
references
References 40 publications
6
417
0
Order By: Relevance
“…Fourth, we used self-report to assign ethnicity, which may result in some misclassification. However, in a separate analysis where we genotyped EpiDREAM participants using a custom-made 50K single nucleotide polymorphism chip for variation in genes related to cardiometabolic risk [36], we found that self-reported ethnicity was strongly correlated with genotype cluster and hence ancestral origin determined by multidimensional scaling [37]. Fifth, we were not able to explore the biological basis of associations and interactions observed in this study.…”
Section: Resultsmentioning
confidence: 64%
“…Fourth, we used self-report to assign ethnicity, which may result in some misclassification. However, in a separate analysis where we genotyped EpiDREAM participants using a custom-made 50K single nucleotide polymorphism chip for variation in genes related to cardiometabolic risk [36], we found that self-reported ethnicity was strongly correlated with genotype cluster and hence ancestral origin determined by multidimensional scaling [37]. Fifth, we were not able to explore the biological basis of associations and interactions observed in this study.…”
Section: Resultsmentioning
confidence: 64%
“…All study subjects were genotyped using the IBC 50K SNP array. 19 Our previous SNP pairwise interaction analysis on this data set reveals that a number of SNPs in CETP significantly interact with several SNPs in BCAT1. It is well known that CETP promotes the transfer of cholesteryl esters from HDL to low-density lipoprotein, and individuals that are genetically deficient for CETP often have extremely high HDL levels.…”
Section: Application To the Hdl Data Setmentioning
confidence: 80%
“…The decreasing cost of genotyping over time also allowed the IBC 50k CAD Consortium to revisit the candidate gene approach using a customized chip that comprehensively surveyed common genetic variation at ~2,100 candidate genes, representing a diverse spectrum of cardiovascular diseases (71). Well-powered studies using this array firmly established associations between CAD and genetic variants in LPA, the gene encoding lipoprotein(a), and confirmed several early GWAS discoveries for CAD (9p21, COL4A1/COL4A2, ZC3HC1, and CYP17A1) (72,73).…”
Section: Discovery Of the First Locus Predisposing To Common Presentamentioning
confidence: 99%